Covid-19 Infection, Postmortem Process and Burial Procedures - Ünüvar Göçeoğlu, Ümit; Yıldırım, Satuk Buğra; Ekinci, Ecesu; Balcı, Yasemin (The Bulletin of Legal Medicine, 2020)
With the outbreak of COVID-19 infection in China in December 2019, the virus started a rapidly spreading pandemia around the world, causing serious health problems and deaths. As of the beginning of March 2020, it has been reported to be seen in over a hundred countries across the world. In our country, the first COVID-19 case was detected at the beginning of March, and the number of death cases has exceeded one thousand to date. In this process, forensic medicine specialists and workers face serious risk of transmission in a possible COVID-19 death. This study is a compilation of the definition and epidemiology of the virus causing Covid-19 disease, how to diagnose of postmortem, postmortem examination and possible risks associated with such a case in the autopsy room and how to reduce these risks. In addition, suggestions regarding burials procedureswere also presented in case of suspicion of Covid-19 infection.